129k views
2 votes
Solve for x

3(ax + 9) = -4 (-2 - 10x)

Solve for x 3(ax + 9) = -4 (-2 - 10x)-example-1

1 Answer

4 votes

Answer:

19

----- = x

40-3a

Explanation:

3(ax + 9) = -4 (-2 - 10x)

Distribute

3ax +27 = 8+40x

Subtract 3ax from each side

3ax-3ax +27 = 8+40x-3ax

27 = = 8+40x-3ax

Subtract 8 from each side

27-8 = 8-8+40x-3ax

19 = 40x-3ax

Factor an x on the right side

19 = x(40-3a)

Divide each side by 40-3a

19/(40-3a) = x(40-3a)/(40-3a)

19

----- = x

40-3a

User Nthalk
by
5.5k points